ASSESSING THE IMPLEMENTATION OF KAMPUS MENGAJAR POLICY IN ISLAMIC EDUCATIONAL INSTITUTIONS - Rahmawati, Rita; Sastrawan, Berry; Martin, Abraham Yazdi; Roestamy, Martin; Purnamasari, Irma; Maruapey, Muhamad Husein; Ramdhani, Muhammad Rendi; Danil, Mahmud (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
This research investigates the implementation of Kampus Mengajar policies from the perspective of Islamic religious values. The study aims to analyze how these policies align with Islamic teachings, particularly in fostering social responsibility and educational development. Using descriptive analysis methods, the research involved 17 students participating in the Kampus Mengajar program, with data collected through questionnaires, in-depth interviews, participatory observation, and literature review. The findings reveal that the overall implementation of Kampus Mengajar policies is rated at 3.84, categorized as Good, with the highest score in the Disposition dimension (4.08) and the lowest in the Resources dimension (3.55). Notably, the facility indicator in the Resources dimension received a lower score (2.65) due to limited infrastructure. Despite these challenges, the program positively impacts schools with insufficient teaching staff, fostering creativity and innovation in the learning process. The study concludes that Kampus Mengajar is significantly aligned with Islamic principles, particularly in terms of social justice and responsibility, and enhances students' knowledge and contributions to educational quality, reflecting devotion to God and service to humanity. This research highlights the importance of integrating Islamic values in policy implementation to improve education.